Enhanced electrical and thermal properties of expanded graphite-polyphenylene sulfide (PPS) composites through in-situ polymerization for fuel cell bipolar plates - Kim, Junghwan; Song, Sun Gu; You, Nam-Ho; Kim, Seo Gyun; Ku, Bon-Cheol (Elsevier, 2025)
This study presents a novel method for synthesis of an expanded graphite (EG) and polyphenylene sulfide (PPS) composite via in-situ polymerization to finely disperse EG, thereby preventing agglomeration and improving conductivity. We achieved high electrical (130 S cm- 1 ) and thermal (28 W m- 1 K-1) conductivity (the polymer content of 60 wt%) striking a balance between conductivity and mechanical properties. The EG-PPS composite was processed via hot-press compression, making it scalable and cost-effective for fuel cell applications. Gas permeability tests confirmed its low permeation rate, validating the composite's suitability for proton exchange membrane fuel cells (PEMFCs) as lightweight, efficient bipolar plates. This method opens possibilities for applying different carbon materials and matrix systems to other fuel cell environments.